Reliability of altitude-induced performance changes in a Top-2 Tour de France cyclist - Bellenou, S.; Quiclet, J.-B.; Millet, G. (Journal of Science and Cycling, 2017)
Assessing fitness changes of athletes is challenging in elite sports (Muller et al. 2000): firstly, tests require a high level of validity, reliability, accessibility and specificity (Hopkins 2000). Secondly, frequent maximal testing sessions are not possible since it would alter the training program and induce additional fatigue. Thirdly, individual responses to an exercise training program are highly variable and influenced by a multitude of determinants and interactions between factors affecting training efficacy. Overall, sharpshooting approach (e.g. investigation of elite athlete)(Mujika 2015) is therefore not only appropriate but necessary for assessing the effectiveness of altitude training.